Self‐reported side‐effects associated with use of dietary supplements in an armed forces population. Issue 3 (2nd November 2015) - Austin, Krista G.; Farina, Emily K.; Lieberman, Harris R.
Abstract : Approximately 60–70% of Armed Forces personnel consume a dietary supplement (DS) at least once a week and there have been numerous reports of severe adverse events among DS users. This study assessed patterns of DS use and self‐reported side‐effects among 4400 Armed Forces personnel using a paper‐and‐pencil survey. Multivariable logistic regression was used to examine associations between patterns of DS use and self‐reported side‐effects. Sixty‐nine percent of personnel surveyed reported using a DS. Seven percent of DS users reported experiencing abnormal heart beats, 6% tremors, 5% stomach pain, 3% dizziness, and 3% numbness/tingling and they believed these symptoms were associated with the use of DS. After adjustment for use of other DS classes, total supplement use, and demographic characteristics, protein supplement users were more likely than non‐users to report numbness/tingling; combination product users were more likely to report experiencing abnormal heart beats, stomach pain, dizziness, tremors, and numbness/tingling; and users of purported steroid analogues were more likely to report dizziness. Use of more than one DS per week was associated with an increased likelihood of reporting side‐effects. Respondents with a higher body mass index were more likely to report side‐effects. Further research is necessary to determine whether self‐reported side‐effects associated with multiple DS use and some DS classes impact the long‐term health or performance of service members. Surveillance of military populations using surveys like this one may provide a method for detecting adverse health events of DS before they are apparent in the civilian population. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Approximately 60‐70% of Armed Forces personnel regularly consume dietary supplements, and there have been numerous reports of severe adverse events among DS users. This study assessed DS use and associated self‐reported adverse health events with a paper‐and‐pencil survey of 4440 Armed Forces personnel. Seven percent of DS users reported experiencing abnormal heart beats, 6% tremors, 5% stomach pain, 3% dizziness, and 3% numbness/tingling they believed were associated with use of DS. As extent of DS use increased, the likelihood of reporting adverse events increased.